A compact synchronous cellular model of nonlinear calcium dynamics: simulation and FPGA synthesis results - Soleimani,H; Drakakis,EM (IEEE Transactions on Biomedical Circuits and Systems, 2017)
Recent studies have demonstrated that calcium is a widespread intracellular ion that controls a widerange of temporal dynamics in the mammalian body. The simulation and validation of such studies us-ing experimental data would bene t from a fast large scale simulation and modelling tool. This paperpresents a compact and fully recon gurable cellular calcium model capable of mimicking Hopf bifurcationphenomenon and various nonlinear responses of the biological calcium dynamics. The proposed cellularmodel is synthesized on a digital platform for a single unit and a network model. Hardware synthesis,physical implementation on FPGA, and theoretical analysis con rm that the proposed cellular model canmimic the biological calcium behaviors with considerably low hardware overhead. The approach has thepotential to speed up large{scale simulations of slow intracellular dynamics by sharing more cellular unitsin real{time. To this end, various networks constructed by pipelining 10k to 40k cellular calcium units arecompared with an equivalent simulation run on a standard PC workstation. Results show that the cellularhardware model is, on average, 83 times faster than the CPU version.